Nocturnal Pain Is Not an Alarm Symptom for Upper Gastrointestinal Inflammation but May Be an Indicator of Sleep Disturbance or Psychological Dysfunction - Jacob Cindrich; Chance Friesen; Jennifer Schurman; Jennifer Colombo; Craig A. Friesen (Gastrointestinal Disorders, 2023)
Alarm symptoms are widely used in pediatric gastroenterology to discern when abdominal pain needs further workup. Despite wide use, the data supporting the validity of these symptoms are not well established. This study explored one alarm symptom—nighttime waking with pain—and its associations with histologic inflammation of the upper gastrointestinal tract, psychological dysfunction, and disordered sleep. This retrospective study evaluated 240 patients with abdominal pain-related disorders of the gut–brain axis (AP-DGBI). Patients underwent questionnaires related to sleep disturbance, behavioral assessment, and gastrointestinal symptoms, including Rome IV criteria for AP-DGBI. Routine upper endoscopy with standardized biopsies was performed in 205 patients. Endoscopy results showed no association between esophageal, gastric, or duodenal histologic inflammation and nighttime waking with pain. Nocturnal pain was associated with increased scores for both psychological and sleep disorders, including social stress, depression, disorders of initiation and maintenance of sleep (DIMS), disorders of daytime somnolence (DOES), and sleep hyperhidrosis (SHY). This study concluded that nocturnal pain is not a reliable predictor of upper gastrointestinal inflammation but may be a prognosticator for psychological distress and sleep disturbances.